2016
DOI: 10.1016/j.ajme.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-antibiotic synergism to control planktonic and biofilm producing clinical isolates of Pseudomonas aeruginosa

Abstract: Introduction: Pseudomonas aeruginosa (P. aeruginosa) is a highly resistant opportunistic pathogen and is capable of forming biofilms on medical devices. Bacterial biofilms, which are micro-colonies encased in extracellular polysaccharide material are so difficult to be treated by conventional antibiotics. During the last decade, P. aeruginosa phages have been extensively examined as an alternative to antimicrobial agents. The aim of the study was to assess bacteriophageantibiotic combination on planktonic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 28 publications
1
42
1
Order By: Relevance
“…The specificity of antibacteriophage systems makes it unlikely that broad anti-bacteriophage mechanisms will arise, as opposed to the spread of multidrug-resistant efflux pump mechanisms in response to conventional broad-spectrum antibiotic therapy. Finally, other reported benefits of bacteriophage therapy include an ability to exhibit synergy with or restore susceptibility to conventional antimicrobial agents, as observed in this case, and the potential ability to disrupt biofilms (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of antibacteriophage systems makes it unlikely that broad anti-bacteriophage mechanisms will arise, as opposed to the spread of multidrug-resistant efflux pump mechanisms in response to conventional broad-spectrum antibiotic therapy. Finally, other reported benefits of bacteriophage therapy include an ability to exhibit synergy with or restore susceptibility to conventional antimicrobial agents, as observed in this case, and the potential ability to disrupt biofilms (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the killing efficacy of each phage on clinical isolates, a dilution series of bacteriophage preparation was spotted on a bacterial lawn to observe plaque formation (25). Briefly, 100 l of an overnight culture of each A. baumannii isolate was used to individually inoculate 2.5 ml of 0.7% molten top agar (temperature, 50Ā°C).…”
Section: Efficiency Of Plating Of Selected Bacteriophages On Clinicalmentioning
confidence: 99%
“…So far, it has been reported that treating Klebsiella pneumoniae infections with a combination of phage and antibiotic is more successful at limiting the emergence of phageā€resistant pathogen mutants compared to antibiotic alone, even though no difference was observed in the effectiveness to eradicate biofilms (Verma, Harjai, & Chhibber, 2009). Another study found that phageā€“antibiotic combinations were more efficient at eradicating the planktonic and biofilm populations of multiple P.Ā aeruginosa strains compared to antibioticā€alone treatments, but the evolution of resistance was not measured in this study (Nouraldin, Baddour, Harfoush, & Essa, 2016). Of late, it was shown that phageā€“antibiotic combinations can considerably vary in their efficiency to eradicate P.Ā aeruginosa biofilms depending on the specific phage species and the class of antibiotic (Chaudhry etĀ al., 2017).…”
Section: Introductionmentioning
confidence: 68%
“…To explore the defensive function of biofilms in detail, we found that biofilm populations had higher levels of resistance compared to planktonic populations when exposed top selection by phage or antibiotic independently. Aminoglycoside antibiotics, including gentamycin, has been found to be less effective against biofilm than planktonic bacteria, largely due to decreased diffusion of antimicrobial agents through the biofilm matrix (Brockhurst, Buckling, & Rainey, 2006; Nouraldin etĀ al., 2016). We found that control biofilm populations did not show clear resistance to phage or antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Bedi et al [2009] reported that a high concentration of an antibiotic with a phage significantly reduces the bacterial load of biofilm when compared to a phage or an antibiotic alone. The higher resistance of biofilm to ampicillin compared to the planktonic state of P. mirabilis could be attributed to decreased antibiotic diffusion through the extensive biofilm matrix, where there is an increase in alginate synthesis [Nouraldin et al, 2016]. Nevertheless, phages can attach to specific receptors, penetrate, and cause biofilm disruption and cell lysis.…”
Section: Discussionmentioning
confidence: 99%